Long-Term Outcomes of Non-Hormonal Therapies for PCOS - Nadia Zulfiqar, Ayesha Khalid, Aasima Rahman, Anila Mujadid Qureshi, Mehmooda Memon, Samina Waseem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovarian syndrome (PCOS) is a reported condition that affects various aspects of a woman’s endocrine system including her reproductive, metabolic, and dermatologic systems. Despite the traditional approach of managing PCOS with hormonal therapies, a substantial proportion, or even nearly half, of women prefer or need non-hormonal treatment plans, particularly those wishing to conceive or with contraindications to hormonal medications. To assess the long-term clinical and reproductive outcomes of non-hormonal therapies, including lifestyle modification, metformin, and inositol in women with PCOS over 12 months. Methods: This was a prospective study performed at department of Gynaecology and Obstetrics, Allied hospital, Faisalabad from July 2022 to January 2023. A sample of 59 women with PCOS was enrolled, and each was treated using one of the non-hormonal options. Clinical evaluation was done on the parameters of BMI, insulin resistance (HOMA-IR), menstrual cycle, ovulation, hirsutism, acne, pregnancy and overall recovery at the beginning of the study and subsequently after 12 months. Results: There were notable changes in metrics such as menstrual regularity (23.7% to 66.1%, p<0.001), ovulation rates (22.0% to 59.3%, p<0.001), BMI (30.1 to 27.4 kg/m², p=0.003), and HOMA-IR (3.8 to 2.5, p=0.001). Hirsutism and acne symptoms showed improvement as well. Of the married women seeking to conceive, 53.6% succeeded within a year. Conclusion: Non-hormonal therapies yield meaningful long-term improvements in reproductive and metabolic outcomes in PCOS patients. These interventions should be considered viable and effective alternatives, especially for women prioritizing fertility or avoiding hormonal treatments. Keywords: PCOS, non-hormonal therapy, metformin, inositol, lifestyle modification, ovulation, insulin resistance, fertility outcomes